2011
DOI: 10.1021/jp1123585
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Atmospheric HONO Formation: New Pathways for N2O4 Isomerization and NO2 Dimerization in the Presence of Water

Abstract: Isomerization of N(2)O(4) and dimerization of NO(2) in thin water films on surfaces are believed to be key steps in the hydrolysis of NO(2), which generates HONO, a significant precursor to the OH free radical in lower atmosphere and high-energy materials. Born-Oppenheimer molecular dynamics simulations using the density functional theory are carried out for NO(2)(H(2)O)(m), m ≤ 4, and N(2)O(4)(H(2)O)(n) clusters, n ≤ 7, used to mimic the surface reaction, to investigate the mechanism around room temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 21 publications
5
59
0
Order By: Relevance
“…It is currently believed that a major source of nocturnal HONO is the heterogeneous hydrolysis of NO 2 on humid surfaces (e.g., Finlayson-Pitts et al, 2003;Ramazan et al, 2006;de Jesus Medeiros and Pimentel, 2011). Using a 1D chemistry and transport model, Wong et al (2011) showed that this mechanism, together with an accurate description of vertical mixing, is able to successfully explain the nocturnal HONO observations in Houston.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 99%
“…It is currently believed that a major source of nocturnal HONO is the heterogeneous hydrolysis of NO 2 on humid surfaces (e.g., Finlayson-Pitts et al, 2003;Ramazan et al, 2006;de Jesus Medeiros and Pimentel, 2011). Using a 1D chemistry and transport model, Wong et al (2011) showed that this mechanism, together with an accurate description of vertical mixing, is able to successfully explain the nocturnal HONO observations in Houston.…”
Section: Heterogeneous Pathways For Atmospheric Hono Formationmentioning
confidence: 99%
“…Additionally, alternate mechanisms have arisen from AIMD simulations of the reaction with one to seven water molecules. 12 For the reaction of (NO + )(NO 3 − ) with water, a cluster size of (H 2 O) 4 was used based on previous work that established the role of the hydrogen-bonding network in promoting reaction of NO + with water. 16 A similar water configuration was identified solvating the cis-ONONO 2 and trans-ONONO 2 isomers of asym-N 2 O 4 [ Figure 1a,b].…”
Section: Clusters As Models For Reactions Onmentioning
confidence: 99%
“…2NO 2 (g)+H 2 O(l) → HONO(g)+H + (aq)+NO − 3 (aq) (R4) Yabushita et al (2009) andDe Jesus Medeiros andPimentel (2011) further investigated the mechanism with focus on the NO 2 uptake and the kinetics of the initial hydrolysis. The reaction rate constant of Reaction (R4) is difficult to determine in the field but can be estimated with the approach of Alicke et al (2002).…”
Section: Introductionmentioning
confidence: 99%